Deep learning for quality control of surface physiographic fields using satellite Earth observations - T. Kimpson; M. Choulga; M. Chantry; G. Balsamo; S. Boussetta; P. Dueben; T. Palmer (Hydrology and Earth System Sciences, 2023)
A purposely built deep learning algorithm for the Verification of Earth System ParametERization (VESPER) is used to assess recent upgrades to the global physiographic datasets underpinning the quality of the Integrated Forecasting System (IFS) of the European Centre for Medium-Range Weather Forecasts (ECMWF), which is used in both numerical weather prediction and climate reanalyses. A neural network regression model is trained to learn the mapping between the surface physiographic dataset, plus the main meteorologic fields from ERA5, and the MODIS satellite skin temperature observations. Once trained, this tool is applied to rapidly assess the quality of upgrades to the physiographic fields used by land surface schemes. Upgrades which improve the prediction accuracy of the machine learning tool indicate a reduction in the errors in the surface fields used as input to the surface parameterization schemes. Conversely, incorrect specifications of the surface fields decrease the accuracy with which VESPER can make predictions. We apply VESPER to assess the accuracy of recent upgrades to the permanent lake and glacier covers, as well as of planned upgrades to represent seasonally varying water bodies (i.e. ephemeral lakes). We show that, for grid cells where the lake fields have been updated, the prediction accuracy of VESPER in the land surface temperature (as quantified by the mean absolute error) improves by 0.37 K on average, whilst for the subset of points where the lakes have been completely removed and replaced with bare ground, the improvement is 0.83 K. We also show that updates to the glacier cover improve the prediction accuracy by 0.22 K. We highlight how neural networks such as VESPER can assist the research and development of surface parameterizations and their input physiography to better represent Earth’s surface coupled processes in weather and climate models.